Lament żałobny Elektry Sofoklesa w kręgu psychoanalizy - Biernat, Justyna (Slavia Occidentalis, 2015)
The aim of this essay is to provide an analysis of Electra’s funeral laments using a psychoanalytical approach. The modern methodology introduced in the research provides a useful conceptual language for in reassessing the ancient categories related to mourning. The essay is an attempt at describing the funeral monologues and their significance for the dramatic structure, as well as an attempt at analysing the motif of mourning. Electra’s behaviour and statements will be analysed in terms of depression and melancholy, whereas her mourning will be depicted as a process of recovery from trauma.